Empowering Brand Equity: The Strategic Role of Brand Ambassadors and Beauty Campaigns in the Cosmetic Industry - Nur Aysa Azzahra; Donni Junipriansa (Dinasti International Journal of Education Management And Social Science, 2025)
Objective: This study aims to examine the strategic role of brand ambassadors and beauty campaigns in enhancing brand equity within the cosmetic industry. Methodology: This study employs a quantitative approach with SEM-PLS. Data were collected through a structured questionnaire distributed to 100 respondents who are familiar with Wardah Cosmetics and its campaigns. The study investigates the relationships between brand ambassadors, beauty campaigns, and brand equity, drawing on relevant marketing theories. Findings: The results reveal that both brand ambassadors and beauty campaigns significantly and positively affect brand equity. Brand ambassadors enhance consumer trust and emotional connection with the brand, while beauty campaigns improve brand visibility and align with consumer values. These factors contribute to higher brand awareness, stronger brand associations, and an improved perception of quality. Conclusion: The study highlights the critical role of brand ambassadors and beauty campaigns in strengthening brand equity. Effective marketing strategies that leverage these elements can create stronger emotional connections with consumers and increase brand recognition, ultimately improving brand equity in a competitive market.